2021
DOI: 10.3390/foods10122939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixed Starters on Proteolysis and Formation of Biogenic Amines in Dry Fermented Mutton Sausages

Abstract: In this study, by comparing the four groups of sausages, namely, CO (without starter culture), LB (with Lactobacillus sakei), LS (with L. sakei 3X-2B + Staphylococcus xylosus SZ-8), and LSS (with L. sakei 3X-2B + S. xylosus SZ-8 + S. carnosus SZ-2), the effects of mixed starter cultures on physical–chemical quality, proteolysis, and biogenic amines (BAs) during fermentation and ripening were investigated. Inoculation of the mixed starter cultures increased the number of lactic acid bacteria and staphylococci i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
6
13
0
Order By: Relevance
“…The low a w and moisture content can improve the safety of fermented lamb jerky. This article also shows the same results as Wang et al's study of strains on fermented sausage, which used pH and water activity as tests to determine when the starter was added [23].…”
Section: Ph a W And Moisture Contentsupporting
confidence: 55%
See 1 more Smart Citation
“…The low a w and moisture content can improve the safety of fermented lamb jerky. This article also shows the same results as Wang et al's study of strains on fermented sausage, which used pH and water activity as tests to determine when the starter was added [23].…”
Section: Ph a W And Moisture Contentsupporting
confidence: 55%
“…The total biogenic amine content in fermented jerky significantly increased during the roasting period (p < 0.05), and in the ripened product this amounted to 103.39-445.29 mg/kg. Wang et al reported that similar results [23]. The addition of starter BL4-8, CL4-3, and X3-2B reduced the BAs content in fermented lamb jerky.…”
Section: Biogenic Amines Analysismentioning
confidence: 60%
“…A growing part of scientific literature analyzes how specific bacterial consortia can limit or degrade BAs formation [104]. Alvarez and Arribas [105] classified many BAsdegrading bacteria and concluded that amino oxidase activity of some strains of LAB is a criterion to select BAs-degrading bacterial cultures, although same strains can also show decarboxylase activity and therefore form BAs.…”
Section: Biogenic Amines In Processed Meatsmentioning
confidence: 99%
“…The protein hydrolysis index, total volatile base nitrogen, and free amino acid content of meat significantly increased during fermentation [ 20 ]. The trial of Yu et al [ 21 ] verified that degradation of large molecules of myogenic fibronectin and myosin in fermented sausage results in an increase in the concentration of small molecule peptides.…”
Section: Protein Changes In Fermented Meat Productsmentioning
confidence: 99%